2022
DOI: 10.3390/recycling7030035
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Sustainable Use of RAP Materials for Pavement Construction in Oman: A Review

Abstract: The Sultanate of Oman has experienced rapid development over the last thirty years and has constructed environmentally friendly and sustainable infrastructure while it continues to find economical alternative resources to achieve the goals of the Oman 2040 vision. The primary concerns are preserving natural resources and reducing the impact of carbon dioxide (CO₂) emissions on the environment. This review aims to encourage the sustainable use of reclaimed asphalt pavement (RAP) materials in pavement constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…The concerns about the necessity of using natural stone and the application of it to all pavements in Hanoi have been raised. Out of many materials that are locally produced and have previously been used, including brick and compact concrete, and other environmentally friendly materials that are globally well-researched, experimented with, and produced, including pervious or permeable concrete, recycled materials, composite materials, and hybrid materials [19][20][21][22][23], the question of why only natural stone is consistently endorsed by the government has not been answered. The hypothesis is that the government has not been informed about the impacts of natural stone on the environment.…”
Section: Environmental Impactsmentioning
confidence: 99%
“…The concerns about the necessity of using natural stone and the application of it to all pavements in Hanoi have been raised. Out of many materials that are locally produced and have previously been used, including brick and compact concrete, and other environmentally friendly materials that are globally well-researched, experimented with, and produced, including pervious or permeable concrete, recycled materials, composite materials, and hybrid materials [19][20][21][22][23], the question of why only natural stone is consistently endorsed by the government has not been answered. The hypothesis is that the government has not been informed about the impacts of natural stone on the environment.…”
Section: Environmental Impactsmentioning
confidence: 99%
“…In spite of the fact that RAP increase the stiffness and may have a beneficial effect of the rutting resistance at high temperature, the thermal and fatigue cracking behaviour remains partially unclear. In some cases, the addition to a maximum of 20 % by weight may ease the mix design (Al Dughaishi et al, 2022). Sometimes the use of roadways reclaimed asphalt is not allowed for the top layer of highways, while for the lower courses an addition up to 50 % is permitted.…”
Section: Recyclingmentioning
confidence: 99%
“…Especially, a large amount of waste asphalt pavement materials, if not timely recycled, not only take up a lot of land and is a waste of resources, but also pollute the environment [1][2][3]. Studies have shown that the reuse of RAP was significant in saving resources, protecting the environment and achieving sustainable development of the construction industry [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%